Diversity of metazoan endoparasites associated with lizards (Squamata, Lacertilia) in three protected areas and their surrounding zones in northeastern Brazil. - Carvalho, Elvis Franklin Fernandes de (2024)
The Neotropical region harbors a rich reptile biodiversity, especially lizards. However, research on parasite richness in Brazilian lizards still has many gaps. Parasites play a crucial role in ecosystems, and accurate studies are necessary to describe their richness and species composition. Habitat fragmentation caused by human activities threatens biodiversity, including parasites. In this context, protected areas play a fundamental role in biodiversity conservation. We aim to describe the diversity of metazoan endoparasites (helminths and pentastomids) in lizards within three protected areas in Northeast Brazil: Aiuaba Ecological Station (Caatinga), Sete Cidades National Park (Cerrado), and Ubajara National Park (Highland marsh and Caatinga), including surrounding areas. We collected 690 lizards representing 23 species. We recorded 34 parasite taxa, including nematodes (28), trematodes (2), cestodes (2), acanthocephalans (1), and pentastomids (1). Among them, we recorded parasites commonly associated with lizards, such as Strongyluris oscari, and rare parasites, such as Brevimulticaecum sp. and Typhlonema sp. We also observed the presence of trematodes exclusively in highland marsh areas. This study contributes to understanding lizard parasitism in the Neotropical region, presenting 21 new infection records. Additionally, it suggests that trematodes may be related to environmental humidity, emphasizing the importance of faunal surveys for parasite diversity.